Indonesian Land Deed Officials as Gatekeepers Against Land Mafia Practices - Pangestu, Bimo; Karjoko , Lego; Hartanto , Heri (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Land mafia practices remain a serious threat to land administration because they undermine legal certainty, damage public trust, and create economic and social losses for legitimate land rights holders. Specific Background In Indonesia, Land Deed Officials (PPAT) hold statutory authority to issue authentic deeds that become the legal basis for land rights transfer and registration. Knowledge Gap Existing land governance still faces administrative loopholes, weak verification, fragmented data systems, and unclear boundaries between administrative, civil, and criminal accountability for PPAT in land mafia cases. Aims This study analyzes the strategic position and legal accountability of PPAT in preventing land mafia practices and securing legal certainty over land rights. Results The study shows that PPAT functions as a gatekeeper of legality through prudence, strict identity and document verification, certificate checking, professional integrity, and compliance with legal procedures. PPAT accountability may arise administratively, civilly, or criminally depending on the level of fault, intent, negligence, and legal consequences. Digital land administration, interinstitutional data integration, transparent audit systems, and coordination among PPAT, ATR/BPN, law enforcement agencies, and local governments are necessary to close administrative gaps. Novelty The study frames PPAT gatekeeping, proportional accountability, digital verification, and institutional synergy as an integrated legal governance framework against land mafia practices. Implications Strengthening PPAT verification standards, legal protection for good-faith officials, and integrated digital oversight can support a more transparent, accountable, and legally certain land administration system. Highlights: PPAT occupies a central position in validating land transactions through authentic deed issuance. Accountability must be assessed proportionally across administrative, civil, and criminal dimensions. Digital records, data integration, audits, and institutional coordination can reduce document manipulation. Keywords : PPAT, Land Mafia, Legal Certainty, Legal Accountability